Some Characteristics and Fatty Acids Composition of Wild Apricot (Prunus pseudoarmeniaca L.) Kernel Oil - KAYA, CEMAL; KOLA, OSMAN; SERTAC OZER, MEHMET; ALTAN, ALI (Asian Journal of Chemistry, 2010)
In this study, the oil composition and some physical and chemical characteristics of wild apricot (P. pseudoarmeniaca L.) kernel oil (WAO) grown in Turkey were determined. Wild apricot kernel contain about 48-50 % crude oil of total dry matter. The oil consist of 93 % of unsaturated fatty acids and the main fatty acids are oleic (75 %), linoleic (17.5 %), palmitic (4.5 %) and stearic (2 %) acids. The other characteristics of the wild apricot oil are approximately as follows: refractive index (20 ºC), 1.469; specific gravity, 0.914 g/cm3; insoluble matter in the ether, 0.5 %; unsaponifiable matter, 0.7 % and iodine value, 92.